2017
DOI: 10.1111/oik.04249
|View full text |Cite
|
Sign up to set email alerts
|

Whether larval amphibians school does not affect the parasite aggregation rule: testing the effects of host spatial heterogeneity in field and experimental studies

Abstract: Almost all macroparasites show over‐dispersed infections within natural host populations such that most parasites are distributed among a few heavily‐infected individuals. Despite the importance of parasite aggregation for understanding system stability, the potential for population regulation, and super‐spreading events, many questions persist about its underlying drivers. Theoretically, aggregation results from heterogeneity in host exposure, resistance, and tolerance. However, few studies have examined how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Taylor [35] suggested that the slope was not only a true population statistic, but also an 'index of aggregation' that described an intrinsic property of the organisms concerned. Consequently, the slope has been used by a number of authors as the basis for a measure of aggregation [8,10,[36][37][38][39][40][41][42][43]. While the methodology has been used to explore the relationship between the distribution of parasites and biologically meaningful covariates [21], it is far from clear how the slope from Taylor's law relates to other concepts of aggregation.…”
Section: Taylor's Lawmentioning
confidence: 99%
“…Taylor [35] suggested that the slope was not only a true population statistic, but also an 'index of aggregation' that described an intrinsic property of the organisms concerned. Consequently, the slope has been used by a number of authors as the basis for a measure of aggregation [8,10,[36][37][38][39][40][41][42][43]. While the methodology has been used to explore the relationship between the distribution of parasites and biologically meaningful covariates [21], it is far from clear how the slope from Taylor's law relates to other concepts of aggregation.…”
Section: Taylor's Lawmentioning
confidence: 99%
“…the residual variance in host body size after accounting for mean host body size), log-host density, and spatial heterogeneity in host density within the pond (i.e. the residual variance in amphibians captured per dipnet sweep after accounting for mean density; see [50] and electronic supplementary material for calculations). At the parasite level, we included parasite body mass, rspb.royalsocietypublishing.org Proc.…”
Section: (C) Analysis Of Aggregationmentioning
confidence: 99%
“…All treatments received three snails (Stagnicola elodes) collected from a field site in Waterloo, Ontario (N43.476450, W80.554990). These were contained in mesh cylinders (15.2 x 14 cm) that rested at the bottom of each bin to prevent their escape (Figure 2-1), but the mesh size (0.32 cm) was sufficient to easily allow passage by cercariae and has been successfully used in other studies (e.g., Koprivnikar et al, 2018). This ensured that the treatments requiring cercariae (C + D) had a constant influx present in the form of infected snails; treatments not requiring cercariae (A + B) had uninfected snails added to account for any possible effect of snail presence irrespective of parasites.…”
Section: Experimental Design and Proceduresmentioning
confidence: 99%